Influence of surrounding gas temperature on thermocouple measurement - Budong Liu; Qinhuang Huang; Peiyong Wang (Case Studies in Thermal Engineering, 2020)
When thermocouples are used to measure gas temperature, the measured temperature, i.e., the thermocouple bead temperature, is not equal to the gas temperature. The bead temperature results from the bead energy balance including the convection with the gas flow, the radiation with the environment and the gas, the conduction with the thermocouple wires. The wire temperature is determined by its own energy balance relating to the gas temperature contacting the wire. Through the wire conduction, the bead temperature is in fact related to the gas temperature surrounding the bead. The influence of the surrounding gas temperature on the thermocouple bead temperature is studied numerically with the one-dimensional code here. The effect length, which is the size of the influencing region, is identified and its relation with the flow condition and the thermocouple property are analyzed. Analytical expressions are also deducted to calculate the effect length. The analytical and numerical results show very good agreement. The analytical effect length follows the same trend as the numerical value when the size and thermal conductivity of the thermocouple and the velocity and temperature of the incoming gas are varied. The analytical effect length deviates from the numerical value by less than 14.3%. Keywords: Thermocouple, Gas temperature measurement, Bead temperature, Wire temperature, Effect length